2006
DOI: 10.1177/0363546506290666
|View full text |Cite
|
Sign up to set email alerts
|

An Allogenic Cell–Based Implant for Meniscal Lesions

Abstract: This study demonstrates the potential of a tissue-engineered cellular repair of the meniscus using autologous and allogenic chondrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 38 publications
2
69
0
2
Order By: Relevance
“…76 Allogenic and xenogeneic cell sources have shown promise in animal models, and although they may overcome the discrepancy in supply and demand, they are fraught with translational issues. 77,78 MSCs, in contrast, have been successfully isolated from adipose tissue, muscle, and bone marrow and subsequently used in soft tissue engineering. 79 It is important to be aware that bone marrow aspirate, concentrated (bone marrow aspirate concentrate [BMAC]) or otherwise, does not equate to using a purified or cultured collection of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…76 Allogenic and xenogeneic cell sources have shown promise in animal models, and although they may overcome the discrepancy in supply and demand, they are fraught with translational issues. 77,78 MSCs, in contrast, have been successfully isolated from adipose tissue, muscle, and bone marrow and subsequently used in soft tissue engineering. 79 It is important to be aware that bone marrow aspirate, concentrated (bone marrow aspirate concentrate [BMAC]) or otherwise, does not equate to using a purified or cultured collection of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is extremely difficult to obtain a sufficient number of autologous meniscus cells from patients who have already undergone meniscectomy. For these reasons, both autologous and allogenic chondrocytes have been used in the replacement of menisci [14,15].…”
Section: Chondrocytes and Fibroblastsmentioning
confidence: 99%
“…These studies were performed ectopically, in a subcutaneous environment in a nude mouse model, which is vascularised and not subjected to weight bearing, and therefore not suitable to ultimately evaluate the value of a regenerative strategy for the knee joint. In order to test the potential of transplanted chondrocytes for use as a reparative technique in lesions involving the human knee, further studies were performed in situ in a pig model (Peretti et al, 2004;Weinand et al, 2006a;Weinand et al, 2006b). Among the animal models for meniscus regeneration studies (Deponti et al, 2013), the pig is very valuable as it has been demonstrated that the vascularisation of the porcine meniscus remains confined in the outer part of the menisci and never extends into the inner third of its structure (Peretti et al, 2004).…”
Section: Cell-based Bonding Studiesmentioning
confidence: 99%
“…According to these results, in subsequent studies the potential of different allogeneic cell sources and of Vicryl meshes as a scaffold was evaluated, in the same orthotopic model as the previous study (Weinand et al, 2006a;Weinand et al, 2006b). The rationale of using allogeneic cells of different sources is that it is unlikely to obtain a sufficient number of healthy meniscal fibrochondrocytes from an injured meniscus.…”
Section: Cell-based Bonding Studiesmentioning
confidence: 99%